Edukasi Pertanian Sehat: Mitigasi Dampak Pestisida dan Genetic Modified Organism - Nur Endah Wahyuningsih; Sulistiyani Sulistiyani; Budiyono Budiyono; Septiria Irawati; Suhartono Suhartono; Muhammad Auliya Rahman; Aldi Prastya Kurniawan; Nethi Puspita Sari; Jessyca Widya Pratiwi; Pingkan Resa Zaskia; Septiana Rahmawati; Kayla Hana Syahidah; Amalia Adiningsih (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Synthetic pesticide exposure remains a significant environmental health concern in Semarang Regency, particularly among farmers who rely heavily on chemical inputs. Although some farmers in Ketapang Village have begun adopting organic practices, their understanding of healthy farming and pesticide-related risks is still limited. This study aimed to strengthen the capacity of the Al Barokah Farmer Group through education and training on healthy farming practices, health risk mitigation related to chemical pesticides, and basic concepts of GMOs. The intervention included presentations, discussions, learning modules, and Focus Group Discussions to explore participants’ perspectives. Effectiveness was evaluated by comparing pre-test and post-test scores and analyzing changes across question components. Results showed an increase in average knowledge scores from 67.64 to 77.92. Eleven of Eightteen items (61.11%) demonstrated improved correct responses, particularly on pesticide use, local microorganisms (MOL), and liquid organic fertilizer (POC). Statistical testing yielded a p-value of 0.011, indicating a significant improvement in participants’ knowledge. These findings highlight the effectiveness of structured education in enhancing farmers’ understanding and support the adoption of safer and more sustainable agricultural practices. The results also identify key topics requiring further emphasis in future training programs.